2021
DOI: 10.3390/app11104550
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Augmented Reality Technologies for Autism Spectrum Disorder Interventions: A Systematic Literature Review

Abstract: Over the past decade, enhanced computing capabilities and mobile technologies have begotten the upsurge of innovative mobile health (mHealth) solutions, and many research efforts have occurred recently in the area of technology-based interventions (TBI) for autism spectrum disorders (ASD). Mobile augmented reality (MAR) refers to AR systems that use the handheld mobile device medium (mobile phones, tablets or smart glasses). This article reports the results of a systematic review undertaken on the use of MAR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 78 publications
(102 reference statements)
1
23
0
Order By: Relevance
“…Few apps have obtained an assessment of "not recommendable", since most apps were found in the "recommendable" group, with an average quality -as Hanna et al (2021) also found in their study -but with potential for improvement in terms of quality, design, pedagogic aspects and content aimed at children and adolescents with autism. Furthermore, these results are in agreement with the findings of Dattolo and Luccio (2017) and Lian and Sunar (2021), which show that the design and content could be improved, as they were not wholly adapted to the needs and characteristics of people with ASD.…”
Section: Discussionsupporting
confidence: 87%
“…Few apps have obtained an assessment of "not recommendable", since most apps were found in the "recommendable" group, with an average quality -as Hanna et al (2021) also found in their study -but with potential for improvement in terms of quality, design, pedagogic aspects and content aimed at children and adolescents with autism. Furthermore, these results are in agreement with the findings of Dattolo and Luccio (2017) and Lian and Sunar (2021), which show that the design and content could be improved, as they were not wholly adapted to the needs and characteristics of people with ASD.…”
Section: Discussionsupporting
confidence: 87%
“…They do not report the specific number of participants. In this line, there are strong similarities with the work of Lian and Sunar (2021) who in 55% of the studies have chosen samples with a maximum of five participants for the development of the work. The reasons for the low number of participants in the samples analysed are varied.…”
Section: Discussionmentioning
confidence: 97%
“…(2021). In the case of motor and navigation skills it also occupies the second position in frequency for the work of Lian and Sunar (2021). By contrast, in the work of Berenguer et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical factor that makes technology successful is the application software ('apps') installed. Designers must ensure that the apps have high interactivity and be of good quality, meet users' needs, and have an effective learning framework [19,20]. It is challenging to find one that is suitable for ASD intervention [21,22].…”
Section: Introductionmentioning
confidence: 99%